GAMBARAN RISIKO PEKERJAAN PETUGAS PEMADAM KEBAKARAN DI DINAS PENCEGAH PEMADAM KEBAKARAN (DP2K) KOTA MEDAN - Rahmi Shafwani (Lingkungan dan Kesehatan Kerja, 2012)
Descriptive of Firefighter Job Risk at Dinas Pencegah Pemadam Kebakaran (DP2K) Medan.The development ofanurban areahas broughta number ofimportant issues, such asthe threat offire hazard. Theauthorized institutionstotacklefiresisthe fire department. The purposeof this studywas to determine thejob riskfaced byfirefightersin Dinas Pencegah Pemadam Kebakaran(DP2K) Medanby using aqualitativeapproach. Dataobtained fromin-depthinterviewswithmembers ofDP2K Medan at Technical Unit I using voice recorder.The results showed the job riskoffirefightersmostlywhen they go to the location of fire,theriskof traffic,andwhen they extinguishfire at thelocation of fire. Job risk at fire location likeaccidentsdue toelectricity, heat, fire, working at height, equipmentoutages, explosions, backdraftandflashover,the condition ofthe buildingon fire,sharp objects, andphysical fightswithpeople. Health complaintsthattheyfeel ingeneralis caused bymanyof the firesmoke inhalationsuch as cough, shortness ofbreath, nausea, vomiting, dizziness, eye irritation, andlimp.GovernmentandDP2KMedan expected toincrease the amount ofPersonal Protective Equipment (PPE). Firefightersare expected to alwaysusing PPEon dutyfirefightingto minimizeunwanted risks. DP2KMedanexpected to increasecooperationwith the policeanddepartment of transportationtomanagethe traffic especially whenthe fire truckwill pass the road towards the location of fire. Keywords : Job Risk, Firefighters